2006
DOI: 10.1007/s00586-005-1037-9
|View full text |Cite
|
Sign up to set email alerts
|

Validity and interobserver agreement of a new radiographic grading system for intervertebral disc degeneration: Part II. Cervical spine

Abstract: A new radiographic grading system for a more objective assessment of lumbar intervertebral disc degeneration has been described and tested in Part I of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…The degrees of degeneration were evaluated from the CT images by two independent radiologists and an orthopedic spine surgeon, who were not informed about this research. According to a fourpoint scale 19) , degeneration was graded as 0 (no signal change), 1 (slight decrease in signal intensity in nucleus pulposus), 2 (distinct decrease in signal intensity in nucleus pulposus with normal disc height), and 3 (severe decrease in signal intensity in nucleus pulposus with disc space narrowing). This scale resulted in a classification of degenerative disorders as non-existent, mild, moderate, and severe, respectively.…”
Section: Subjectsmentioning
confidence: 99%
“…The degrees of degeneration were evaluated from the CT images by two independent radiologists and an orthopedic spine surgeon, who were not informed about this research. According to a fourpoint scale 19) , degeneration was graded as 0 (no signal change), 1 (slight decrease in signal intensity in nucleus pulposus), 2 (distinct decrease in signal intensity in nucleus pulposus with normal disc height), and 3 (severe decrease in signal intensity in nucleus pulposus with disc space narrowing). This scale resulted in a classification of degenerative disorders as non-existent, mild, moderate, and severe, respectively.…”
Section: Subjectsmentioning
confidence: 99%
“…The fifth point on this scale (fissured) was not used because it required fluid to be injected into the intact disc for positive identification. Inspection of the radiographs showed that these four grades are equivalent to grades 0-3 on the scale proposed for radiographic assessment of cervical discs [18]. Disc area was estimated from the anteroposterior and lateral diameters of the lower endplate of the upper vertebra in each motion segment, using the formula for the area of an ellispse (p · a · b/4) where the diameters a and b were measured from radiographs.…”
Section: Morphologymentioning
confidence: 99%
“…21,[31][32][33][34][35] It is worth noting the use of the same parameters for degeneration -the presence of osteophytes, the loss of disc height, and subchondral sclerosis -qualified in such a way as to be used for the composition of grading schemes regarding the severity of the clinical profile presented by the patient. (Table 3) Pathria et al 36 developed a grading system based on degenerative facet changes identified in oblique radiographs and CT. Weishaupt et al 37 correlated changes in CT with those found in MRI, using the parameters of facet joint space, articular hypertrophy, and the presence of osteophytes to define their grades.…”
Section: Resultsmentioning
confidence: 99%
“…Kettler et al 35 proposed a new grading system for cervical degeneration, similar to the one developed for the lumbar spine by Wilke et al 21 They evaluated the loss of disc height and the presence of osteophytes and subchondral sclerosis, and they compared the radiographic scores with the structural changes found macroscopically after dissecting the pieces. The value of the Kappa coefficient found was 0.688.…”
Section: Discussionmentioning
confidence: 99%